Production of Nigella sativa Beverage Powder under Foam Mat Drying Using Egg Albumen as a Foaming Agent - Affandi, Norhazirah; Zzaman, Wahidu; Yang, Tajul Aris; Mat Easa, Azhar (MDPI AG, 2017)
The aim of this study was to determine the feasibility of producing Nigella sativa powder under a foam mat drying technique. A central, composite design of experiments was used to optimize the drying condition and compare the solubility, the antioxidant and mineral content of roasted Nigella sativa, and the foam mat dried Nigella sativa powder. Foams were prepared from Nigella sativa solution by adding different concentrations of egg albumen (2.5%, 8.75%, and 15% w/w) and methyl cellulose (0, 0.5% and 1% w/w), using whipping times of 2, 5, and 8 min. The drying temperature was set at 50–70 C, with a foam thickness of 1, 2, and 3 mm. The optimum recorded conditions for the foaming process were 15% of egg albumen concentration, 0.69% of methyl cellulose concentration, and a whipping time of 8 min. Thus, the optimum conditions for the drying process were 60 C, with 2 mm of foam thickness. The results showed that there were significant differences in DPPH inhibition, the total phenolic content, and mineral content, whereas no significant differences were recorded in the water solubility index between the roasted Nigella sativa and the foam mat dried Nigella sativa powder.